Alcohol use severity and depressive symptoms among late adolescent Hispanics: Testing associations of acculturation and enculturation in a bicultural transaction model. (October 2015) - Cano, Miguel Ángel; de Dios, Marcel A.; Castro, Yessenia; Vaughan, Ellen L.; Castillo, Linda G.; Lorenzo-Blanco, Elma I.; Piña-Watson, Brandy; Berger Cardoso, Jodi; Ojeda, Lizette; Cruz, Rick A.; Correa-Fernandez, Virmarie; Ibañez, Gladys; et al.
Abstract: Research has indicated that Hispanics have high rates of heavy drinking and depressive symptoms during late adolescence. The purpose of this study was to test a bicultural transaction model composed of two enthnocultural orientations (acculturation and enculturation); and stressful cultural transactions with both the U.S. culture (perceived ethnic discrimination) and Hispanic culture (perceived intragroup marginalization) to predict alcohol use severity and depressive symptoms among a sample of 129 (men = 39, women = 90) late adolescent Hispanics (ages 18–21) enrolled in college. Results from a path analysis indicated that the model accounted for 18.2% of the variance in alcohol use severity and 24.3% of the variance in depressive symptoms. None of the acculturation or enculturation domains had statistically significant direct effects with alcohol use severity or depressive symptoms. However, higher reports of ethnic discrimination were associated with higher reports of alcohol use severity and depressive symptoms. Similarly, higher reports of intragroup marginalization were associated with higher depressive symptoms. Further, both ethnic discrimination and intragroup marginalization functioned as mediators of multiple domains of acculturation and enculturation. These findings highlight the need to consider the indirect effects of enthnocultural orientations in relation to health-related outcomes. Highlights: Higher ethnic discrimination was associated with higher alcohol use severity. Higher ethnic discrimination was associated with higher depressive symptoms. Higher intragroup marginalization was associated with higher depressive symptoms. Ethnic discrimination functioned as a mediator of acculturation/enculturation. Intragroup marginalization functioned as a mediator of acculturation/enculturation.